The influence of palaeogeography and tectonic events on trilobite distributions in Morocco and northwestern Algeria. (25th May 2022) - Bault, Valentin; Crônier, Catherine; Bignon, Arnaud
Abstract: The effects of sea-level changes and anoxia on Devonian trilobites have been studied for a long time, but the importance of palaeogeographic and tectonic events in this key-period is still not well understood. In the Devonian Period, trilobites invaded many different marine environments and areas in North Africa where important palaeogeographic changes occurred. Distribution patterns of trilobites through time and space have been analysed using a hierarchical cluster analysis and diversity indices. Our examination of the literature suggests that trilobites were scarce during Lochkovian time before an important diversification in Pragian time. Trilobites flourished in many North African regions without there being important taxonomic differences between basins, because of free migration in relatively flat palaeo-topography and homogeneous environments. During Middle Devonian time, early Variscan tectonic movements transformed the eastern Anti-Atlas area into a basin with a platform topography. Geographical barriers such as deep basins prevented trilobite migrations. At the beginning of Eifelian time, the reduction in migration between the different regions of this area coincided with a decrease in diversity. Consequently, tectonic events played an important role in the decline of trilobites during Middle Devonian time, especially when these were combined with sea-level changes and anoxic/hypoxic events. A recovery occurred in Famennian time involving only new genera. As at the global scale, cyrtosymbolines developed in shallow seas, whereas phacopids evolved in deeper environments. The basin and platform system still hampered migrations, although sea-level variations led to episodic exchanges. The late Famennian regression reduced trilobite diversity dramatically in the study area.